Ciencias sociales 9 E.G.B. Tercer Ciclo - ALONSO, María Ernestina; BLANCO, Jorge; FERNANDEZ CASO, María Victoria; CHAVES, Silvia; GUREVICH, Raquel; LEWKOWICZ, Mariana; MAZZEO, Miguel (AIQUE, 2001)
AUTORES: VAZQUEZ, Enrique C.